2013
DOI: 10.2306/scienceasia1513-1874.2013.39.596
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cDNA encoding cystatin with antifungal activity from Siam tulip Curcuma alismatifolia

Abstract: Cystatins are cysteine protease inhibitors involved in defence mechanisms against pests and pathogens. Here, the cystatin CaCPI gene was isolated from a cDNA library of the Siam tulip (Curcuma alismatifolia cv. Chiang Mai Pink was then transformed into Escherichia coli strain BL21-Star to produce a recombinant CaCPI protein. After induction with 1 mM IPTG, the cell lysate of E. coli-carrying pDEST17-CaCPI generated a CaCPI protein about 12 kDa in size as measured using SDS-PAGE. Pre-incubation of the 5-30 µM C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, A. niger was more susceptible, since it required a lesser AhCPI concentration to inhibit spore germination compared with A. parasiticus . Accordingly, it has been suggested that the cystatin inhibitory effect is determined by the fungal species (Porruan et al 2013); this hypothesis is in agreement with this study and others (Joshi et al 1998; Pernas et al 2000; Martínez et al 2003; Valdés-Rodríguez et al 2010). These results may be explained in terms of cell wall organization and composition, which are extremely variable and depend on many factors such as environmental changes, developmental stage, fungal species, etc.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, A. niger was more susceptible, since it required a lesser AhCPI concentration to inhibit spore germination compared with A. parasiticus . Accordingly, it has been suggested that the cystatin inhibitory effect is determined by the fungal species (Porruan et al 2013); this hypothesis is in agreement with this study and others (Joshi et al 1998; Pernas et al 2000; Martínez et al 2003; Valdés-Rodríguez et al 2010). These results may be explained in terms of cell wall organization and composition, which are extremely variable and depend on many factors such as environmental changes, developmental stage, fungal species, etc.…”
Section: Resultssupporting
confidence: 92%
“…The recombinant barley and chestnut cystatin inhibited the growth of Botrytis cinerea, Colletotrichum graminicola, Septoria nodorum and Plectosphaerella cucumerina ; interestingly, it did not affect Trichoderma viride (Pernas et al 2000; Martínez et al 2003). In the case of cystatin from siam tulip, the protein abolished mycelial growth of F. oxysporum, Colletotrichum capsici and Pyricularia grisea at different levels; 5 μM inhibited almost 100% of P. grisea whereas, F. oxysporum and C. capsici required almost 10 μM to reach the same level of inhibition (Porruan et al 2013). The differences in sensivity to cystatin between species could be given by developmental stage and/or cell wall composition (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Hv-CPI1, FaCPI-1 and KCPI, 50% growth inhibition of B. cinerea occurred at concentrations of 1.5 μM, 1.9 μM and 2.7 μM, respectively [ 10 , 42 , 43 ], which are close to that of BnCPI (~1.81 μM). For F. oxysporum , 50% growth inhibition of HvCPI-1, AhCPI and CaCPI occurred at concentrations of 2.14 μM, 2.28 μM and 13 μM, respectively [ 10 , 18 , 44 ]. The 50% growth inhibition of reBnCPI on F. oxysporum was about 7.23 μM, which is higher than that reported for other phytocystatins.…”
Section: Discussionmentioning
confidence: 99%